Increased fasting small-bowel water content in untreated coeliac disease and scleroderma as assessed by magnetic resonance imaging. Issue 10 (December 2019) - Lam, Ching; Sanders, David S; Lanyon, Peter; Garsed, Klara; Foley, Stephen; Pritchard, Susan; Marciani, Luca; Hoad, Caroline L; Costigan, Carolyn; Gowland, Penny; Spiller, Robin
Background and aims: The regular overnight migrating motor complex (MMC) ensures that the normal fasting small-bowel water content (SBWC) is minimised. We have applied our recently validated non-invasive magnetic resonance technique to assess SBWC in newly diagnosed coeliac disease (CD), scleroderma (SCD) and irritable bowel syndrome (IBS), conditions possibly associated with small intestinal bacterial overgrowth (SIBO). Methods: A total of 20 CD and 15 SCD patients with gastrointestinal symptoms were compared to 20 healthy volunteers (HV) and 26 IBS with diarrhoea (IBS-D) patients, as previously reported. All underwent a fasting magnetic resonance imaging (MRI) scan on a 1.5 T Philips Achieva MRI scanner to assess fasting SBWC and colonic volumes. Stool and symptom diaries were completed for one week. Results: Compared to HV, all patients had significantly increased stool frequency and Bristol stool form score. SBWC was significantly increased in CD (median 109 mL; interquartile range (IQR) 53–224 mL) compared to HV (median 53 mL; IQR 31–98 mL; p < 0.01) and IBS-D (median 42 mL; IQR 28–67 mL; p < 0.01). A variable increase in SBWC was also found in SCD (median 77 mL; IQR 39–158 mL), but this was not significant ( p = 0.2). Colonic volumes were similar for all groups, being a median of 547 mL (IQR 442–786 mL) for CD, 511 mL (453–789 mL) for SCD, 612 mL (445–746 mL) for HV and 521 mL (428–757 mL) for IBS-D. When CD patients were subdivided according to the Marsh classification, the higher grades had larger colonic volumes. Conclusion: Fasting SBWC as assessed by MRI is significantly increased in newly diagnosed CD and SCD but decreased in IBS-D. Future studies should test whether increased resting fluid predisposes to SIBO.